2020
DOI: 10.5222/mmj.2020.98048
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Observed in the SARS-CoV-2 Spike Glycoprotein and Their Effects in the Interaction of Virus with ACE-2 Receptor

Abstract: Coronaviruses (CoVs) classified in the Coronaviridae family infect a very large spectrum of vertebrate group. Seven CoVs that cause human disease consist of Alpha-CoVs, which are HCoV-229E, and NL63 and beta-CoVs, which are MERS-CoV, SARS-CoV, HCoV-OC43, HCoV-HKU1, and SARS-CoV-2. SARS-CoV-2 is an enveloped, positive-polarity, single-stranded RNA virus responsible for a new Coronavirus disease 2019 (COVID-19). The mutagenic ability of the SARS-CoV-2 directs its evolution and genome variability, thus allowing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…Live attenuated vaccines (LAVs) are particularly attractive, as they activate all branches of the host immune system (humoral, innate, and cellular) (2,3). Also, a vaccine that can present all SARS-CoV-2 antigens to the host is optimal because it can both induce a broad immune response and is less likely to lose significant potency due to the antigenic drift that we are already witnessing (4)(5)(6).…”
mentioning
confidence: 99%
“…Live attenuated vaccines (LAVs) are particularly attractive, as they activate all branches of the host immune system (humoral, innate, and cellular) (2,3). Also, a vaccine that can present all SARS-CoV-2 antigens to the host is optimal because it can both induce a broad immune response and is less likely to lose significant potency due to the antigenic drift that we are already witnessing (4)(5)(6).…”
mentioning
confidence: 99%
“…The first mutations registered after the initial outbreak in Wuhan are analyzed, i.e. : Y28, A67, N74, W152, Y200, R273, F275, L276, E298, K300, T302, G485, A570, D614, A653, L752, P812, I818, G838, F1103, and V1104 [7][8][9][10][11]. In addition, to corroborate whether the two variants registered in Brazil (until February 2021) could be predicted with the results of the paper, the E484K mutation was initially registered in a patient infected in Rio of Janeiro in October 2020 [3], and later a pool of mutations that occurred in the second Brazilian variant (also known as P. [3].…”
Section: Methodsmentioning
confidence: 99%
“…CRISPR RNAs (crRNAs) can target the SARS-CoV-2 conserved genomic regions, and a bioinformatic analysis by Abbott et al showed that a group of only six crRNAs were more than 90% effective as anti-SARS-CoV-2 agents even though the synthesized fragments were used [ 24 ]. However, it is speculated that the RNAi therapy or the CRISPR-based therapy would be useful if new mutations arise in the viral spike protein-encoding genomes (already 15 amino acid variations have been observed in the RBD of the mutant SARS-CoV-2) which may render the mRNA vaccines or the DNA vaccines inactive against the new strains of SARS-CoV-2 [ 25 , 26 ]. Extensive clinical trials using these two new approaches would be required to prove such an assumption though.…”
Section: Comparative Efficacy Between the Dna And Rna Vaccines And Thmentioning
confidence: 99%